Lightweight temperature-resistant heat-insulating interface adhesive and preparation method thereof
By mixing low-melting point mixture, nano-scale ceramicized mixture and resin matrix to prepare interface glue, the problem of poor thermal insulation and oxidation resistance in high-temperature environments is solved, and the lightweight, low thermal conductivity and high bonding properties of interface glue are achieved, ensuring the overall thermal insulation and oxidation resistance of composite materials.
Patent Information
- Application Number
- CN202411831045.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-25
AI Technical Summary
The existing interface glue has poor thermal insulation and oxidation resistance under high temperature environments, resulting in the resin-based anti-thermal insulation composite materials being prone to debonding at high temperatures, and cannot guarantee the overall thermal insulation and oxidation resistance.
Interface glue is prepared by mixing low-melting point mixture, nano-scale ceramicized mixture and resin matrix. The low-melting point mixture consists of low-melting point glass powder and hollow glass microspheres. The nano-scale ceramicized mixture consists of zirconium diboride, molybdenum disilide, vapor phase silicon dioxide and silicon hexaboride. Lightweight, temperature-resistant and heat-insulating interface glue is prepared through casting and drying processes.
The interface adhesive has the advantages of light weight, low thermal conductivity and low linear ablation rate, and has good bonding properties in high temperature environments, ensuring the overall thermal insulation and oxidation resistance of resin-based anti-insulating composite materials.
Smart Images

Figure BDA0005185560890000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microwave absorbing agent preparation, and in particular to a lightweight temperature-resistant and heat-insulating interface adhesive and a preparation method thereof. Background Art
[0002] At present, interface adhesives are mostly used in cement, laminates and other daily production, but there are few reports on the application of industrial production of thermal insulation composite materials. During the use of resin-based thermal insulation composite materials, in order to adapt to the complex mechanical and thermal environment, the interface adhesive used for bonding needs to have at least three functions: lightweight, as an auxiliary material of resin-based composite materials, its weight needs to be constrained; temperature resistance and ablation resistance, in some special positions, such as the external position of the thermal insulation material, the environment in which the interface adhesive and the matrix material serve is basically similar, and it is necessary to have ablation resistance and oxidation resistance; thermal insulation performance, in order to prevent the heat flow from entering the product rapidly along the bonding area of the interface adhesive, the interface adhesive material needs to have a low thermal conductivity, which can block the entry of heat for a long time. However, the existing interface adhesive has poor thermal insulation and ablation resistance, and it is easy to cause the material to debond at high temperature after being compounded with the resin-based thermal insulation material, thus failing to ensure the overall good thermal insulation and oxidation resistance of the composite material.
[0003] Based on this, there is an urgent need to provide a lightweight, temperature-resistant, heat-insulating interface adhesive and a preparation method thereof. Summary of the invention
[0004] The embodiment of the present invention provides a lightweight, heat-resistant, and heat-insulating interface adhesive and a preparation method thereof, which can solve the problems of poor heat insulation and oxidation resistance of traditional interface adhesives and poor bonding performance in high temperature environments.
[0005] In the first aspect, the present invention provides a lightweight, temperature-resistant, and heat-insulating interface adhesive, the raw materials for preparing the interface adhesive include a low-melting point mixture, a nano-scale ceramic mixture, and a resin matrix; wherein the low-melting point mixture includes a low-melting point glass powder and hollow glass microspheres, and the nano-scale ceramic mixture includes zirconium diboride, molybdenum disilicide, gas-phase silicon dioxide, and silicon hexaboride.
[0006] Preferably, the resin matrix is one of boron-modified phenolic resin, silicon-modified phenolic resin, epoxy-modified phenolic resin, ammonia-free modified phenolic resin or ammonia-modified phenolic resin.
[0007] Preferably, the mass concentration of the resin matrix is 70-90%.
[0008] Preferably, in terms of mass fractions, the low-melting point mixture is 30-50 parts, the nano-scale ceramic mixture is 20-30 parts, and the resin matrix is 80-90 parts.
[0009] Preferably, in the low-melting-point mixture, the mass ratio of the low-melting-point glass powder to the hollow glass microspheres is (4-5):(3-4).
[0010] Preferably, the melting point of the low-melting-point glass powder is 400-600°C.
[0011] Preferably, in the nano-scale ceramic mixture, the mass ratio of zirconium diboride, molybdenum disilicide, fumed silicon dioxide and silicon hexaboride is (8-10): (6-8): (3-5): (2-4).
[0012] Preferably, the average particle size of the nano-scale ceramic mixture is 300-800 nm.
[0013] In a second aspect, the present invention provides a method for preparing the interface adhesive as described in any one of the first aspects above, the preparation method comprising the following steps:
[0014] (1) stirring and mixing low-melting-point glass powder and hollow glass microspheres in proportion to obtain a low-melting-point mixed material;
[0015] (2) mixing zirconium diboride, molybdenum disilicide, fumed silicon dioxide and silicon hexaboride in proportion to obtain a nano-scale ceramic mixture;
[0016] (3) stirring and mixing the low melting point mixture and the nano-scale ceramic mixture, and then stirring and mixing with a resin matrix and an organic solvent in turn to obtain a mixed interface adhesive;
[0017] (4) Casting the mixed interface adhesive and drying it to obtain the lightweight, heat-resistant and heat-insulating interface adhesive.
[0018] Preferably, in step (3), the organic solvent is ethanol, and the content of the organic solvent is 30-50 wt %.
[0019] Preferably, in step (4), the drying temperature is 40-60° C. and the drying time is 6-8 h.
[0020] In a third aspect, the present invention provides a use of the lightweight temperature-resistant thermal insulation interface adhesive described in any one of the first aspects in a resin-based thermal insulation composite material.
[0021] In a fourth aspect, the present invention provides a method for preparing a resin-based composite material using the lightweight temperature-resistant and heat-insulating interface adhesive described in any one of the first aspects above, the method comprising:
[0022] S1. Determine the thickness of the interface glue on the surface of the resin-based thermal insulation composite material;
[0023] S2, coating a layer of interface glue on the surface of the resin-based thermal insulation material, and then drying and cooling in sequence to obtain a first resin-based thermal insulation material;
[0024] S3, repeating step S2 to apply interface glue on the interface glue surface of the first resin-based thermal insulation material until the interface glue on the surface of the resin-based thermal insulation composite material reaches a preset thickness;
[0025] S4, covering the other side of the resin-based thermal insulation material to be bonded onto the surface of the interface adhesive, and after gradient temperature curing, obtaining the resin-based thermal insulation composite material.
[0026] Preferably, the gradient temperature curing includes six stages; wherein, the temperature of the first stage is 75-80°C, and the insulation time is 0.5-1h; the temperature of the second stage is 95-105°C, and the insulation time is 0.5-1h; the temperature of the third stage is 115-125°C, and the insulation time is 1-1.5h; the temperature of the fourth stage is 135-145°C, and the insulation time is 1.5-2.5h; the temperature of the fifth stage is 155-165°C, and the insulation time is 1.5-2.5h; the temperature of the sixth stage is 175-185°C, and the insulation time is 1.5-2.5h.
[0027] Compared with the prior art, the present invention has at least the following beneficial effects:
[0028] In the present invention, the interface adhesive is prepared by mixing a low-melting point mixture, a nano-scale ceramic mixture and a resin matrix. The low-melting point mixture is made by mixing low-melting point glass powder and hollow glass microspheres, so that the mixture can reduce the weight of the interface adhesive and reduce the thermal conductivity on the one hand, and on the other hand, by utilizing its own low-temperature melting characteristics, the interface adhesive can have a good bonding effect during service; at the same time, the nano-scale ceramic mixture is mixed with zirconium diboride, molybdenum disilicide, fumed silica and silicon hexaboride. Under high temperature conditions, the mixture will enter the lightweight heat-insulating composite material or fabric with the resin matrix, and will form a densified surface layer under high temperature conditions, further hindering the entry of oxygen and heat; further, the resin matrix is used as a colloidal substrate, and the low-melting point mixture and the nano-scale ceramic mixture are fused to increase the bonding performance of the interface agent. In this way, the interface adhesive prepared by the present invention has the advantages of light weight, low thermal conductivity and low linear ablation rate, and has good bonding performance under high temperature conditions. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] An embodiment of the present invention provides a lightweight, temperature-resistant, and heat-insulating interface adhesive, the raw materials for preparing the interface adhesive include a low-melting point mixture, a nano-scale ceramic mixture, and a resin matrix; wherein the low-melting point mixture includes a low-melting point glass powder and hollow glass microspheres, and the nano-scale ceramic mixture includes zirconium diboride, molybdenum disilicide, gas-phase silicon dioxide, and silicon hexaboride.
[0031] In the embodiment of the present invention, the interface adhesive is prepared by mixing a low-melting point mixture, a nano-scale ceramic mixture and a resin matrix, and the low-melting point mixture is mixed with a low-melting point glass powder and a hollow glass microsphere, so that the mixture can reduce the weight of the interface adhesive and reduce the thermal conductivity on the one hand, and on the other hand, by utilizing its own low-temperature melting characteristics, the interface adhesive can have a good bonding effect during service; at the same time, the nano-scale ceramic mixture is mixed with zirconium diboride, molybdenum disilicide, gas-phase silica and silicon hexaboride, and the mixture will enter the lightweight heat-insulating composite material or fabric with the resin matrix under high temperature environment, and will form a densified surface layer under high temperature environment, further hindering the entry of oxygen and heat; further, the resin matrix is used as a colloidal substrate, and the low-melting point mixture and the nano-scale ceramic mixture are fused to increase the bonding performance of the interface agent. In this way, the interface adhesive prepared by the present invention has the advantages of light weight, low thermal conductivity and low linear ablation rate, and has good bonding performance under high temperature environment.
[0032] According to some preferred embodiments, the resin matrix is one of boron-modified phenolic resin, silicon-modified phenolic resin, epoxy-modified phenolic resin, ammonia-free modified phenolic resin or ammonia-modified phenolic resin; the mass concentration of the resin matrix is 70-90% (for example, it can be 70%, 75%, 80%, 85% or 90%).
[0033] In an embodiment of the present invention, the above-mentioned modified type of phenolic resin is used as a resin matrix to fuse a low-melting point mixture and a nano-ceramic mixture, and the mass concentration of the resin matrix is reasonably controlled. This is beneficial to ensuring that the interface adhesive has better temperature resistance and ablation resistance, and can ensure that the interface adhesive has a stronger interface bonding performance with the interface to be bonded after curing while ensuring lightness.
[0034] It should be noted that, in the embodiments of the present invention, the above-mentioned types of modified phenolic resins can be purchased from the market.
[0035] According to some preferred embodiments, in parts by mass, the low-melting point mixture is 30-50 parts (for example, it can be 30 parts, 35 parts, 40 parts, 45 parts or 50 parts), the nano-scale ceramic mixture is 20-30 parts (for example, it can be 20 parts, 22 parts, 25 parts, 28 parts or 30 parts), and the resin matrix is 80-90 parts (for example, it can be 80 parts, 82 parts, 85 parts, 88 parts or 90 parts).
[0036] The present invention has been experimentally confirmed that the reasonable control of the quality of the low melting point mixture, the nano-ceramic mixture and the resin matrix is conducive to ensuring that the prepared interface glue has both light weight, high temperature resistance, ablation resistance and oxidation resistance, so that the interface glue can have excellent bonding performance under high temperature environment. If the content of the low melting point mixture is too low, the weight of the interface glue will be increased, which is not conducive to ensuring the good thermal insulation and bonding performance of the interface glue, and if the content of the low melting point mixture is too high, it is not conducive to ensuring the good oxidation resistance and ablation resistance of the interface glue; the appropriate content of the nano-ceramic mixture can make the interface glue have good oxidation resistance and ablation resistance, and if the content of the nano-ceramic mixture is too much, the lightness of the interface glue will be sacrificed to a large extent; further, the appropriate content of the resin matrix is conducive to the uniform fusion of the low melting point mixture and the nano-ceramic mixture, and further enhances the oxidation resistance and ablation resistance of the interface glue, and if the content of the resin matrix is too much, the density of the interface glue will be increased, which is also not conducive to ensuring the lightness of the interface glue.
[0037] According to some preferred embodiments, in the low-melting point mixture, the mass ratio of the low-melting point glass powder and the hollow glass microspheres is (4-5):(3-4) (for example, it can be 4:3, 4:4, 5:3 or 5:4); the melting point of the low-melting point glass powder is 400-600°C (for example, it can be 400°C, 500°C or 600°C).
[0038] In the embodiment of the present invention, the low-melting-point glass powder has a melting property at low temperature (400-600°C). After melting at 400-600°C, the interface adhesive can have good bonding performance during service. The hollow glass microspheres are light and have heat-insulating properties. They are mixed with the low-melting-point glass powder in a certain mass ratio, so that the interface adhesive can have both light weight and good heat-insulating properties.
[0039] According to some preferred embodiments, in the nano-scale ceramic mixture, the mass ratio of zirconium diboride, molybdenum disilicide, fumed silicon dioxide and silicon hexaboride is (8-10): (6-8): (3-5): (2-4) (for example, 8:6:3:2, 8:7:3:2, 8:6:4:2, 8:6:3:3, 9:7:4:3, 9:7:3:2, 9:6:3:2, 9:8:5:4, 10:8:5:4 or 10:6:3:2); the average particle size of the nano-scale ceramic mixture is 300-800nm (for example, 300nm, 400nm, 500nm, 600nm, 700nm or 800nm).
[0040] In the embodiment of the present invention, zirconium diboride, molybdenum disilicide, fumed silica and silicon hexaboride are used together as a nano-scale ceramic mixture. The particle size of the mixture is small. At low temperature (400-600°C), the low-melting point glass powder can melt and bond the zirconium diboride and silicon hexaboride with the resin matrix into the resin-based thermal insulation material to be bonded (lightweight thermal insulation material or fabric), thereby ensuring that the interface adhesive has good bonding performance at low temperatures. Furthermore, at high temperatures (600-1000°C), fumed silica and molybdenum disilicide will form a densified surface layer on the surface of the resin-based thermal insulation material to be bonded, thereby preventing the entry of oxygen and heat, thereby ensuring that the interface adhesive has good anti-ablation and anti-oxidation properties in a high temperature environment; in this way, through the reasonable control of the types and contents of the above components, the excellent bonding performance of the interface adhesive in a wide temperature range environment is effectively guaranteed.
[0041] The present invention also provides a method for preparing the interface adhesive described in any one of the above items, the preparation method comprising the following steps:
[0042] (1) stirring and mixing low-melting-point glass powder and hollow glass microspheres in proportion to obtain a low-melting-point mixed material;
[0043] (2) mixing zirconium diboride, molybdenum disilicide, fumed silicon dioxide and silicon hexaboride in proportion to obtain a nano-scale ceramic mixture;
[0044] (3) stirring and mixing the low melting point mixture and the nano-scale ceramic mixture, and then stirring and mixing with a resin matrix and an organic solvent in turn to obtain a mixed interface adhesive;
[0045] (4) Casting the mixed interface adhesive and drying it to obtain the lightweight, heat-resistant and heat-insulating interface adhesive.
[0046] In an embodiment of the present invention, in order to ensure that each component is evenly dispersed in the interface adhesive, first, the low-melting point glass powder and the hollow glass microspheres are stirred and mixed in proportion for 30-35 minutes, and zirconium diboride, molybdenum disilicide, fumed silica and silicon hexaboride are also stirred and mixed in proportion for 30-35 minutes. After mixing, they are dried at room temperature to obtain a low-melting point mixture and a nano-scale ceramic mixture; thereafter, the two are stirred and mixed for about 60 minutes, put into a resin matrix, and an appropriate amount of organic solvent is added to dilute the colloid, and the mixed interface adhesive is obtained after stirring and mixing. Through the above process, the components can be fully mixed, thereby ensuring that the performance of each area of the lightweight, heat-resistant and heat-insulating interface adhesive obtained by the final cast and leveling is uniform.
[0047] It should be noted that, in the embodiment of the present invention, the thickness of the interface glue after casting is 1-5 mm, preferably 2-3 mm.
[0048] According to some preferred embodiments, in step (3), the organic solvent is ethanol, and the content of the organic solvent is 30-50wt% (for example, it can be 30wt%, 40wt% or 50wt%); in step (4), the drying temperature is 40-60°C (for example, it can be 40°C, 50°C or 60°C), and the time is 6-8h (for example, it can be 6h, 7h or 8h).
[0049] In an embodiment of the present invention, during the process of preparing the interface adhesive, a certain amount of organic solvent is used to disperse the various components, and the organic solvent can evaporate during use, thereby ensuring that the various components are evenly dispersed without adversely affecting the bonding properties of the interface adhesive. If the content of the organic solvent is too much, the interface adhesive will debond during use.
[0050] An embodiment of the present invention further provides a use of the lightweight temperature-resistant thermal insulation interface adhesive described in any one of the above items in a resin-based thermal insulation composite material.
[0051] The interface adhesive in the embodiment of the present invention has the properties of light weight, heat insulation, oxidation resistance and ablation resistance, and can be applied to resin-based heat insulation composite materials to ensure good bonding performance of the composite materials at high temperatures.
[0052] The embodiment of the present invention further provides a method for preparing a resin-based composite material using the lightweight temperature-resistant and heat-insulating interface adhesive described in any one of the above items, the method comprising:
[0053] S1. Determine the thickness of the interface glue on the surface of the resin-based thermal insulation composite material;
[0054] S2, coating a layer of interface glue on the surface of the resin-based thermal insulation material, and then drying and cooling in sequence to obtain a first resin-based thermal insulation material;
[0055] S3, repeating step S2 to apply interface glue on the interface glue surface of the first resin-based thermal insulation material until the interface glue on the surface of the resin-based thermal insulation composite material reaches a preset thickness;
[0056] S4, covering the other side of the resin-based thermal insulation material to be bonded onto the surface of the interface adhesive, and after gradient temperature curing, obtaining the resin-based thermal insulation composite material.
[0057] In an embodiment of the present invention, in the process of preparing a resin-based thermal insulation composite material by bonding a resin-based thermal insulation material with an interface adhesive, a layer of interface adhesive is first coated on the surface of the resin-based thermal insulation material or fabric to be bonded, and then the entire thing is placed in an oven at a temperature of 60-70°C for drying for about 2 hours, so that the interface adhesive is softened. The softened interface adhesive can partially penetrate into the resin-based thermal insulation material or fabric, and it is placed at room temperature (25°C) for condensation. Then, a layer of interface adhesive is repeatedly placed on the surface of the interface adhesive and the drying and condensation are repeated until a preset thickness is reached. In this way, the thickness of the interface adhesive in the resin-based thermal insulation composite material can be accurately controlled. Finally, another side of the resin-based thermal insulation material or fabric is placed on the surface of the interface adhesive, and the resin-based thermal insulation composite material is obtained after curing.
[0058] According to some preferred embodiments, the gradient temperature curing includes six stages; wherein, the temperature of the first stage is 75-80°C, and the insulation time is 0.5-1h; the temperature of the second stage is 95-105°C, and the insulation time is 0.5-1h; the temperature of the third stage is 115-125°C, and the insulation time is 1-1.5h; the temperature of the fourth stage is 135-145°C, and the insulation time is 1.5-2.5h; the temperature of the fifth stage is 155-165°C, and the insulation time is 1.5-2.5h; the temperature of the sixth stage is 175-185°C, and the insulation time is 1.5-2.5h.
[0059] In the embodiment of the present invention, by using six gradient temperatures to cure the resin-based composite material of the bonding interface glue, the interface glue can be fully cured, thereby ensuring the adhesion of the interface glue between the two layers of resin-based thermal insulation materials to the greatest extent, thereby ensuring the better overall performance of the resin-based thermal insulation composite material.
[0060] In order to more clearly illustrate the technical solution and advantages of the present invention, a lightweight, heat-resistant and heat-insulating interface adhesive and a preparation method thereof are described in detail below through several embodiments.
[0061] Embodiment 1:
[0062] (1) 450 parts of low-melting-point glass powder and 350 parts of hollow glass powder were stirred for 30 minutes, and after being mixed evenly, they were dried at room temperature (25° C.) to obtain a low-melting-point mixture;
[0063] (2) 90 parts of zirconium diboride, 70 parts of molybdenum disilicide, 40 parts of fumed silicon dioxide and 30 parts of silicon hexaboride were stirred for 30 minutes, mixed evenly and then dried at room temperature to obtain a nano-ceramic mixture (average particle size of 550 nm);
[0064] (3) After stirring 40 parts of the low-melting point mixture and 25 parts of the nano-ceramic mixture for 60 minutes, the mixture was added into 85 parts of a resin matrix (silicon-modified phenolic resin with a mass concentration of 80%), and then an organic solvent (ethanol) was added and stirred for 30 minutes to obtain a mixed interface adhesive; wherein the content of the organic solvent in the mixed interface adhesive was 40wt%;
[0065] (4) After the mixed interface adhesive is cast and leveled, it is placed in an oven and dried at 50° C. for 6 hours to obtain a lightweight, heat-resistant, and heat-insulating interface adhesive.
[0066] Embodiment 2:
[0067] (1) 400 parts of low-melting-point glass powder and 300 parts of hollow glass powder were stirred for 30 minutes, and after being mixed evenly, they were dried at room temperature (25° C.) to obtain a low-melting-point mixture;
[0068] (2) 90 parts of zirconium diboride, 70 parts of molybdenum disilicide, 40 parts of fumed silicon dioxide and 30 parts of silicon hexaboride were stirred for 30 minutes, mixed evenly and then dried at room temperature to obtain a nano-ceramic mixture (average particle size of 550 nm);
[0069] (3) After stirring 30 parts of the low-melting point mixture and 30 parts of the nano-ceramic mixture for 60 minutes, the mixture was placed in 90 parts of a resin matrix (silicon-modified phenolic resin with a mass concentration of 80%), and then an organic solvent (ethanol) was added and stirred for 30 minutes to obtain a mixed interface adhesive; wherein the content of the organic solvent in the mixed interface adhesive was 40wt%;
[0070] (4) After the mixed interface adhesive is cast and leveled, it is placed in an oven and dried at 50° C. for 6 h to obtain a lightweight, heat-resistant, and heat-insulating interface adhesive.
[0071] Embodiment 3:
[0072] (1) 500 parts of low-melting-point glass powder and 400 parts of hollow glass powder were stirred for 30 minutes, and after being mixed evenly, they were air-dried at room temperature (25° C.) to obtain a low-melting-point mixture;
[0073] (2) 90 parts of zirconium diboride, 70 parts of molybdenum disilicide, 40 parts of fumed silicon dioxide and 30 parts of silicon hexaboride were stirred for 30 minutes, mixed evenly and then dried at room temperature to obtain a nano-ceramic mixture (average particle size of 550 nm);
[0074] (3) After stirring 50 parts of the low-melting point mixture and 20 parts of the nano-ceramic mixture for 60 minutes, the mixture was placed in 80 parts of a resin matrix (silicon-modified phenolic resin with a mass concentration of 80%), and then an organic solvent (ethanol) was added and stirred for 30 minutes to obtain a mixed interface adhesive; wherein the content of the organic solvent in the mixed interface adhesive was 40wt%;
[0075] (4) After the mixed interface adhesive is cast and leveled, it is placed in an oven and dried at 50° C. for 6 h to obtain a lightweight, heat-resistant, and heat-insulating interface adhesive.
[0076] Embodiment 4:
[0077] Example 4 is basically the same as Example 1, except that in step (3), the content of the low melting point mixture is 60 parts.
[0078] Embodiment 5:
[0079] Example 5 is basically the same as Example 1, except that in step (1), in the low-melting point mixture, the mass ratio of the low-melting point glass powder to the hollow glass microspheres is 6:3.5, that is, when preparing the low-melting point mixture, the content of the low-melting point glass powder is 600 parts, and the content of the hollow glass microspheres is 350 parts.
[0080] Embodiment 6:
[0081] Example 6 is basically the same as Example 1, except that in step (2), in the nano-scale ceramic mixture, the mass ratio of zirconium diboride, molybdenum disilicide, gas-phase silica and silicon hexaboride is 3:9:7:3, that is, when preparing the nano-scale ceramic mixture, the content of zirconium diboride is 30 parts, the content of molybdenum disilicide is 90 parts, the content of gas-phase silica is 70 parts, and the content of silicon hexaboride is 30 parts.
[0082] Embodiment 7:
[0083] Example 7 is substantially the same as Example 1, except that in step (3), the content of the organic solvent in the mixed interface glue is 90 wt %.
[0084] Embodiment 8:
[0085] Example 8 is substantially the same as Example 1, except that in step (3), the content of the organic solvent in the mixed interface glue is 5 wt %.
[0086] Comparative Example 1:
[0087] Comparative Example 1 is basically the same as Example 1, except that in step (3), 40 parts of the low-melting point mixture are placed in 85 parts of a resin matrix (silicon-modified phenolic resin with a mass concentration of 80%), and then an organic solvent (ethanol) is added and stirred for 30 minutes to obtain a mixed interface adhesive; wherein the content of the organic solvent in the mixed interface adhesive is 40wt%.
[0088] Comparative Example 2:
[0089] Comparative Example 2 is basically the same as Example 1, except that in step (3), 25 parts of the nano-ceramic mixture are placed in 85 parts of a resin matrix (silicon-modified phenolic resin with a mass concentration of 80%), and then an organic solvent (ethanol) is added and stirred for 30 minutes to obtain a mixed interface glue; wherein the content of the organic solvent in the mixed interface glue is 40wt%.
[0090] Comparative Example 3:
[0091] Comparative Example 3 is substantially the same as Example 1, except that the interface adhesive only includes a resin matrix (silicon-modified phenolic resin having a mass concentration of 80%).
[0092] Comparative Example 4:
[0093] Comparative Example 4 is substantially the same as Example 1, except that in step (1), the low-melting-point mixture only includes low-melting-point glass powder.
[0094] Comparative Example 5:
[0095] Comparative Example 5 is substantially the same as Example 1, except that in step (1), the low melting point mixture only includes hollow glass microspheres.
[0096] Comparative Example 6:
[0097] Comparative Example 6 is substantially the same as Example 1, except that in step (2), the nano-scale ceramic mixture only includes zirconium diboride and silicon hexaboride.
[0098] The performance of the lightweight, heat-resistant, and heat-insulating interface adhesives prepared in Examples 1 to 8 and Comparative Examples 1 to 6 was tested, and the test results are shown in Table 1.
[0099] Performance test method: The density of the interface glue is tested with reference to GB / T 30904 "Determination of apparent density of foam plastics and rubber", the thermal conductivity is tested with reference to GB / T 10295-2008 "Determination of steady-state thermal resistance and related properties of insulation materials, heat flow meter method", and the line ablation rate is tested with reference to GJB 323B-2018 "Oxygen-acetylene ablation test method";
[0100] In order to further verify the performance of the interface adhesive prepared by the present invention, the interface adhesive in the above embodiments and comparative examples was used to bond the lightweight thermal protection material and the fabric, and the flat tensile performance of the composite material was tested with reference to GB / T 1452-2018 "Test method for flat tensile strength of sandwich structure".
[0101] Table 1
[0102]
[0103] Note: “ / ” indicates that the performance cannot be tested;
[0104] As can be seen from Table 1, compared with the comparative example, the interface adhesive prepared by mixing the low melting point mixture, the nano-ceramic mixture and the resin matrix in the embodiment of the present invention has light weight, excellent thermal insulation and ablation resistance, and has excellent bonding performance in a high temperature environment. In Example 6, the content of zirconium diboride and silicon hexaboride in the nano-ceramic mixture is low, and the content of molybdenum disilicide and fumed silicon dioxide is too high, which not only increases the density of the composite material, but also easily causes stratification during low-temperature ablation.
[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A lightweight, heat-resistant, and heat-insulating interface adhesive, characterized in that: The raw materials for preparing the interface adhesive include a low-melting point mixture, a nano-scale ceramic mixture and a resin matrix; wherein the low-melting point mixture includes a low-melting point glass powder and hollow glass microspheres, and the nano-scale ceramic mixture includes zirconium diboride, molybdenum disilicide, gas-phase silicon dioxide and silicon hexaboride.
2. The interface adhesive according to claim 1, characterized in that: The resin matrix is one of boron-modified phenolic resin, silicon-modified phenolic resin, epoxy-modified phenolic resin, ammonia-free modified phenolic resin or ammonia-modified phenolic resin; and / or The mass concentration of the resin matrix is 70-90%.
3. The interface adhesive according to claim 1, characterized in that: In terms of mass fractions, the low melting point mixed material accounts for 30-50 parts, the nano-scale ceramic mixed material accounts for 20-30 parts, and the resin matrix accounts for 80-90 parts.
4. The interface adhesive according to claim 1, characterized in that: In the low-melting-point mixture, the mass ratio of the low-melting-point glass powder to the hollow glass microspheres is (4-5): (3-4); and / or The melting point of the low-melting-point glass powder is 400-600°C.
5. The interface adhesive according to claim 1, characterized in that: In the nano-scale ceramic mixture, the mass ratio of zirconium diboride, molybdenum disilicide, fumed silicon dioxide and silicon hexaboride is (8-10): (6-8): (3-5): (2-4); and / or The average particle size of the nano-scale ceramic mixture is 300-800nm.
6. A method for preparing an interface adhesive according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) stirring and mixing low-melting-point glass powder and hollow glass microspheres in proportion to obtain a low-melting-point mixed material; (2) mixing zirconium diboride, molybdenum disilicide, fumed silicon dioxide and silicon hexaboride in proportion to obtain a nano-scale ceramic mixture; (3) stirring and mixing the low melting point mixture and the nano-scale ceramic mixture, and then stirring and mixing with a resin matrix and an organic solvent in turn to obtain a mixed interface adhesive; (4) Casting the mixed interface adhesive and drying it to obtain the lightweight, heat-resistant and heat-insulating interface adhesive.
7. The preparation method according to claim 6, characterized in that: In step (3), the organic solvent is ethanol, and the content of the organic solvent is 30-50wt%; and / or In step (4), the drying temperature is 40-60° C. and the drying time is 6-8 hours.
8. Use of the lightweight temperature-resistant thermal insulation interface adhesive according to any one of claims 1 to 5 in a resin-based thermal insulation composite material.
9. A method for preparing a resin-based composite material using the lightweight temperature-resistant and heat-insulating interface adhesive according to any one of claims 1 to 5, characterized in that: The method comprises: S1. Determine the thickness of the interface glue on the surface of the resin-based thermal insulation composite material; S2, coating a layer of interface glue on the surface of the resin-based thermal insulation material, and then drying and cooling in sequence to obtain a first resin-based thermal insulation material; S3, repeating step S2 to apply interface glue on the interface glue surface of the first resin-based thermal insulation material until the interface glue on the surface of the resin-based thermal insulation composite material reaches a preset thickness; S4, covering the other side of the resin-based thermal insulation material to be bonded onto the surface of the interface adhesive, and after gradient temperature curing, obtaining the resin-based thermal insulation composite material.
10. The method according to claim 9, characterized in that The gradient temperature curing includes six stages; Among them, the temperature of the first stage is 75-80℃, and the insulation time is 0.5-1h; the temperature of the second stage is 95-105℃, and the insulation time is 0.5-1h; the temperature of the third stage is 115-125℃, and the insulation time is 1-1.5h; the temperature of the fourth stage is 135-145℃, and the insulation time is 1.5-2.5h; the temperature of the fifth stage is 155-165℃, and the insulation time is 1.5-2.5h; the temperature of the sixth stage is 175-185℃, and the insulation time is 1.5-2.5h.